THE BEAUTY – FIRST WAY OF KNOWING: SOME GENERAL OBSERVATIONS ON THE ROLE OF THE AESTHETIC IN ACCURATE COGNITION AND IN THE PRACTICE OF CHRISTIAN SPIRITUALITY (Annals of the University of Bucharest. Philosophy Series, 2025)
Human cognition functions best when it traces a path across the three Socratic transcendentals in the unfolding sequence of Beauty, then Goodness, then Truth. I therefore describe the ideal approach to knowledge as “Beauty-First.” By analogizing the epistemological progression underlying the classical Trivium, the Eastern Orthodox Philokalia, and the method that made science truly modern, and then noting that this structure seems to be corroborated by the neuroscience of Iain McGilchrist, we seem to confirm the hypothesis that Beauty, Goodness, and Truth must be appropriated in this sequence in a concentric unfolding of human attention.
Keywords: Trivium; beauty; beauty-first; Philokalia; epistemology; Iain McGilchrist; brain hemispheres; natural philosophy; science and beauty